Vietnam : Governance and Administration of Social Assistance - A Rapid Assessment and Options for Reform - World Bank (Washington, DC, 2013)
The coverage of social assistance in Vietnam is expected to expand over the coming years in line with Government plans for further strengthening social security. This raises the question of whether the governance and administrative arrangements for social assistance at all levels are sufficiently robust to handle a larger program. This note provides a rapid assessment of the arrangements for delivering Vietnam's main social assistance program, social assistance under Decrees 67 and 13, and proposes options for further strengthening in the short and medium term. It aims to make a timely contribution to the ongoing policy discussions about strengthening social assistance as part of the implementation of the Social Security Strategy 2011-2020. The note reflects findings from visits to Ha Giang Province and Ho Chi Minh City in July 2010. It finds that the current delivery mechanisms for social assistance are basic, with limited human resources, no caseload management and no integrated database that would allow tracking of beneficiary numbers. While such basic governance and administrative arrangements may be appropriate for a small program such as social assistance under Decree 67 in the past, the expected increase in beneficiary coverage implies that program administration will have to be systematically strengthened and professionalized to ensure effective implementation. Moreover, the development of a modern system of social policy in Vietnam will also require the expansion of skills in social work, in particular of those currently involved in delivering social assistance and who will remain the main interface to current and prospective beneficiaries at the local level.